The textual dimension of didactics: formation of future teachers’ philological competence - Moldir E. Toiganbekova; Gulmira A. Kazhigaliyeva; Ainur A. Bizhanova (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study provides a theoretical and conceptual evaluation of text as an integrative didactic resource essential for developing the professional readiness of future teachers. Addressing the need for structured didactic tools in competence-based teacher education, the research aims to theoretically substantiate and evaluate the didactic role of text in developing philological competence. The methodology adopts a theoretical evaluative approach, combining structural-functional text analysis with a systematic analysis of competence components. By utilizing literature analysis, content analysis, and interpretive analysis, the study evaluates the educational functions of text without empirical data collection from participants. The analytical findings indicate that text functions as a system-forming didactic factor, supporting the integrated development of linguistic, speech, textual, communicative, cultural, and reflective components. The evaluation suggests that diverse text practices, including popular science and case studies, provide conditions for facilitating critical thinking and productive writing skills through analysis, interpretation, and reconstruction. This study contributes a theoretically grounded “text→philological competence→professional readiness” model that evaluates how text-centric activity facilitates holistic professional readiness. The findings offer a transferable framework for informing curriculum design and supporting the development of text-centered instructional strategies in modern teacher education.